1985
DOI: 10.1104/pp.77.3.731
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Light and Temperature on the Fluence Response Curves for Germination of Rumex obtusifolius

Abstract: Both red light (10 minutes) and 35°C treatment (60 minutes) stimulate the germination of seeds of Rumex obtusifolius otherwise maintained in darkness at 25°C. Fluence response curves were determined for the effect of red light to stimulate germination of seeds with and without 35°C treatment. The endogenous far-red absorbing form (Pfr) level in the seeds was determined using short saturating fluences of wavelengths of light which maintain different proportions of phytochrome as Pfr at equilibrium. In the seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
0
11
0
2
Order By: Relevance
“…This effect of light promoting cactacean seed germination was reported in Pachycereus pringlei (Nolasco et al, 1996) Smith (1975) reported the same effect of temperature on light sensitivity by seeds in Lactuca sativa. At 45°C few seeds of H. setaceus germinated and did not show light sensitivity, probably due to an overriding factor not related to phytochrome (Takaki et al, 1985). Two hours photoperiod was enough to induce maximum germination at 25°C with highest germination rate with increasing photoperiod (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This effect of light promoting cactacean seed germination was reported in Pachycereus pringlei (Nolasco et al, 1996) Smith (1975) reported the same effect of temperature on light sensitivity by seeds in Lactuca sativa. At 45°C few seeds of H. setaceus germinated and did not show light sensitivity, probably due to an overriding factor not related to phytochrome (Takaki et al, 1985). Two hours photoperiod was enough to induce maximum germination at 25°C with highest germination rate with increasing photoperiod (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…No escuro, as sementes de V. glandulifera mantiveram baixa percentagem de germinação em todas as temperaturas (máximo de 25%), enquanto V. gigantea e V. variabilis, nas temperaturas mais altas, apresentaram percen-tagens de germinação semelhantes às obtidas na luz. De acordo com Taylorson & Hendricks (1972) e Takaki et al (1985) a temperatura pode causar alterações da sensibilidade da semente a baixos níveis de Fve pré-existentes, favorecendo a germinação no escuro, fato que poderia explicar as elevadas percentagens de germinação dessas espécies no escuro, em temperaturas mais altas.…”
Section: Discussionunclassified
“…Examinando Takaki et al (1985), segundo os quais a temperatura pode causar alterações da sensibilidade da semente a baixos níveis de Fve pré-existentes, favorecendo a germinação no escuro, fato que pode explicar as elevadas porcentagens de germinação das espécies D. insularis e D. ciliaris no escuro, sob temperaturas mais elevadas. De forma semelhante, Carvalho et al (2005) estudaram aspectos relacionados à germinação do capim-branco (Chloris polydactyla), identificando maiores percentuais de germinação em presença de luz, interagindo com a alternância de temperatura.…”
Section: Tabela 1 Porcentagem E íNdice De Velocidade De Germinação (unclassified